2020
DOI: 10.1136/bmjopen-2019-033234
|View full text |Cite
|
Sign up to set email alerts
|

Midlife socioeconomic position and old-age dementia mortality: a large prospective register-based study from Finland

Abstract: ObjectivesTo assess the association between multiple indicators of socioeconomic position and dementia-related death, and to estimate the contribution of dementia to socioeconomic differences in overall mortality at older ages.DesignProspective population-based register study.SettingFinland.Participants11% random sample of the population aged 70–87 years resident in Finland at the end of year 2000 (n=54 964).Main outcome measureIncidence rates, Kaplan-Meier survival probabilities and Cox regression HRs of deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 25 publications
5
17
0
1
Order By: Relevance
“…These findings add to mounting evidence that socioeconomic status is an important determinant of dementia risk (2)(3)(4)(5)(6) . Although a direct causal relationship between socioeconomic status and dementia has yet to be established, stratification of other dementia risk factors within more deprived groups would still suggest that deprivation could be a major target in public health approaches aimed at reducing the population burden of dementia.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…These findings add to mounting evidence that socioeconomic status is an important determinant of dementia risk (2)(3)(4)(5)(6) . Although a direct causal relationship between socioeconomic status and dementia has yet to be established, stratification of other dementia risk factors within more deprived groups would still suggest that deprivation could be a major target in public health approaches aimed at reducing the population burden of dementia.…”
Section: Discussionsupporting
confidence: 58%
“…However, the association of this with dementia mortality across the United Kingdom has not been systematically examined. Socioeconomic deprivation has previously been shown to be a risk factor for dementia (2)(3)(4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%
“…These findings add to mounting evidence that socioeconomic status is an important determinant of dementia risk (2)(3)(4)(5)(6) . Our results highlight that deprivation should be considered a major target in public health approaches aimed at reducing the population burden of dementia.…”
Section: Discussionsupporting
confidence: 58%
“…Socioeconomic deprivation has previously been shown to be a risk factor for dementia (2)(3)(4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Socioeconomic status (SES), commonly measured by educational level, income level, and occupation, has been recognized as a risk factor for dementia and dementia-related death given that low SES was found to be associated with an increased risk for both. [8][9][10][11][12][13] Aside from studies on the risk of developing dementia, few studies have focused on SES and its association with dementia diagnosis and cognitive severity at diagnosis. Findings of such studies generally showed that lower SES was associated with a higher risk of receiving a dementia diagnosis and lower cognitive function at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 99%